RELEVANSI NILAI DIVIDEND YIELD DAN RASIO P/E DENGAN PERTUMBUHAN PERUSAHAAN - Julianto Agung Saputro (Faculty of Economics and Business, Universitas Gadjah Mada, 2002)
Analysts use valuation model in determining and evaluating share prices. Survey evidence suggests that the dominant valuation model is the price-earnings (P/E) ratio, but that other approaches such as the dividend yield are also important. This study develops and tests a market valuation models whose main prediction is that equity value is a function of earnings, dividends and book value. This study demonstrates that growth firms relevant use P/E ratio approach, and that not growth firms more relevant use dividend yield ratio approach than P/E ratio.Keywords: P/E ratio, dividend yield, market valution model, growth firm